Review artikel: validasi metode analisis kadar parasetamol dalam sediaan obat menggunakan berbagai instrumen - Zanuba, Anisa; Permatasari, Lina; Febrianingsih, Karlina Dwi; Anindiya, Naya Wahyu; Razkianita, Haulya; Mustika, Mitha Juliana (Universitas Mataram, 2025)
Paracetamol is one of the analgesic-antipyretic drugs that has been widely used by the public as a first-line treatment. The level of paracetamol in each preparation must comply with the standards set in the Indonesian Pharmacopoeia so that it is necessary to determine the level. This study aims to evaluate the validation of the analysis method for paracetamol levels in various drug preparations using three main instruments: infrared spectrophotometry (FTIR), ultraviolet spectrophotometry (UV-Vis), and high-performance liquid chromatography (HPLC). Validation was carried out based on the parameters of accuracy, precision, limit of detection (LOD), and limit of quantification (LOQ). The results showed that the three instruments met the validation requirements set by the Indonesian Pharmacopoeia, with FTIR showing the best precision (RSD 0.03%), UV-Vis having the highest accuracy (% recovery 106.95%), and HPLC having the highest sensitivity with a LOD value of 0.76 Âµg/mL. For the levels of paracetamol with various dosage forms and instruments, the average results obtained meet the requirements, namely between 90%-110%. Overall, these methods are effective for the analysis of paracetamol levels, providing accurate and consistent results according to pharmacopoeial standards. Based on the review results, the instrument that mostly meets all the requirements for validation of the analysis method is HPLC.